Autoimmune Movement Disorders - Fearon, Conor; O'Toole, Orna (Seminars in Neurology, 2018)
Autoimmune movement disorders are rare but potentially treatable entities. They can present with an excess or paucity of movement and may have other associated neurological symptoms. These disorders were originally recognized by their classic clinical presentations and the cancers associated with them. Recent emphasis has been targeted on associated, and sometimes causative, antibodies. Although some disorders have stereotypical presentations, the spectrum of abnormalities reported in association with antibodies is widening. Determining whether antibodies are incidental or pathogenic and, hence, foregoing or commencing immunotherapy treatment can be challenging for practicing neurologists. Physicians often have to make the decision to empirically treat patients while awaiting test results. Due to the lack of randomized controlled trials, the ideal immunotherapy treatments and regimens are unknown. Patients with intracellularly targeted antibodies tend to fare less well, while those with extracellularly targeted antibody disorders often respond to treatments reducing antibody production. This review aims to summarize reported adult-onset autoimmune movement disorders to date, and to provide a template for the workup and treatment of suspected disorders. Rarer antibodies that are not yet fully characterized, or reported in a few cases only, will not be covered in detail as these are not likely to be readily commercially available. Childhood disorders will be only be mentioned briefly in the discussion, as there is a separate article in this issue on autoimmune neurologic diseases in children.
Keywords: autoimmune; encephalitis; movement disorder; paraneoplastic